A novel and efficient synthesis of phenanthrene derivatives via palladium/norbornadiene-catalyzed domino one-pot reaction - Zhong, Yue; Wu, Wen-Yu; Yu, Shao-Peng; Fan, Tian-Yuan; Yu, Hai-Tao; Li, Nian-Guang; Shi, Zhi-Hao; Tang, Yu-Ping; Duan, Jin-Ao (Beilstein Journal of Organic Chemistry, 2019)
Herein we report a novel palladium-catalyzed reaction that results in phenanthrene derivatives using aryl iodides, ortho-bromobenzoyl chlorides and norbornadiene in one pot. This dramatic transformation undergoes ortho-C–H activation, decarbonylation and subsequent a retro-Diels–Alder process. Pleasantly, this protocol has a wider substrate range, shorter reaction times and higher yields of products than previously reported methods.
Keywords: C–H activation; norbornadiene; palladium; phenanthrene derivatives